A Blockchain-Based Public Key Infrastructure For IoT-Based Healthcare Systems - Joseph Antony, Amalan; Singh, Kunwar (Computer journal, 2024)
Secure exchange of data among the various stake holders of healthcare systems is of prime importance. As the size of the healthcare networks grew, several variants of Public Key Infrastructures (PKIs) were proposed as a means to achieve reliable authentication, confidentiality, non-repudiation, etc. The most prevalent approach to PKI has been the use of Certificate Authorities (CAs). But, events like the breach of the CA DigiNotar, and the ensuing fake certificates for Google, among other noteworthy high-profile domains, has cast doubts on the reliability of a CA, and therefore on PKIs modelled as CAs too. In this paper, we propose a new approach to a healthcare PKI modelled on a blockchain, incorporating Elliptic Curve Cryptographic methods for secure key generations.